Active Learning dalam Pembelajaran Matematika SD Melalui Permainan Engklek Mamun - Khasanah, Ulfatun (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2020)
The weak ability of the students on the summation material and reduction in the background of this research. Mathematics is abstract, so in mathematics learning the necessary medium/intermediary that serves to confine so that facts clearer and more easily accepted by students. Media used is the game usually Mamun, which is a game conducted in groups in the form of advanced crank if the number of positive and crank backward if the number is negative. Numbers is a row of students holding positive and negative number flags. Each student holds a number. Students who do not hold the number do the forward or backward crank according to the prescribed number. The method is qualitative. The result is that through the game Engklek Mamun students can do the counting operation summation and reduction on the number line.